Improving the Competitive Advantage of BUMDes Based on The Optimal Utilization of Local Assets Communities - Condro Puspo Nugroho; Deny Meitasari; Destyana Ellinggga Pratiwi; Vi'in Ayu Pertiwi (HABITAT, 2020)
BUMDes is one of the income sources for the village managing assets, services, and other businesses for the village community's welfare.Â BUMDes empowers rural communities as an autonomous region in increasing productive efforts to alleviate poverty and unemployment. Therefore, the measurement of BUMDes's performance needs to be done through the level of local resources used and the implications of the results achieved. It was required to formulate appropriate development policies so that BUMDes have high competitiveness and fulfill their role in increasing the community's economic independence. This study was conducted in East Java BUMDes because East Java province is the third province with the largest number of BUMDes in Indonesia, so it was quite representative to represent the presence of BUMDes in Indonesia. This research used a quantitative approach carried out using the structural equation modeling-partial least square (SEM-PLS) method with the Resource-based View (RBV) approach to measure the effect of BUMDes resources used on its competitiveness. The analysis showed that structural capital had a positive effect on human capital and relational capital. Human capital had also been proven to have a positive effect on relational capital. The indicator that influenced competitive advantage was human capital. Training is needed to increase the human resources capacity, online marketing training and organizational reform, infrastructure, and professional management systems need to be done.